Gold Nanoparticles Synthesized Using Extracts of Cyclopia intermedia, Commonly Known as Honeybush, Amplify the Cytotoxic Effects of Doxorubicin - Aboyewa, Jumoke A. (Nanomaterials (Basel), 2021)
Cyclopia intermedia (C. intermedia) is an indigenous South African shrub used to prepare the popular medicinal honeybush (HB) tea. This plant contains high levels of mangiferin (MGF), a xanthonoid that was reported to have numerous biological activities, including anti-tumor activity. MGF and extracts that contain high concentrations of MGF, such as extracts from Mangifera indica L. or mango have been used to synthesize gold nanoparticles (AuNPs) using green nanotechnology. It has previously been shown that when AuNPs synthesized from M. indica L. extracts are used in combination with doxorubicin (DOX) and Ayurvedic medicine, the anti-tumor effects appear to be augmented. It has also been demonstrated that MGF used in combination with DOX resulted in enhanced anti-tumor effects. In this study, C. intermedia (HB) and MGF were used to synthesize HB-AuNPs and MGF-AuNPs, respectively. The physicochemical properties of the AuNPs were characterized by the UV-Visible Spectroscopy (UV-Vis), dynamic light scattering (DLS), Fourier transform infra-red spectroscopy (FTIR), X-ray diffraction spectroscopy (XRD) and high-resolution transmission electron microscopy (HR-TEM). The cytotoxicity of HB-AuNPs and MGF-AuNPs were assessed on human colon (Caco-2), prostate (PC-3) and glioblastoma (U87) cancer cells; as well as normal breast epithelial (MCF-12A) cells using the MTT assay. Both HB-AuNPs and MGF-AuNPs demonstrated relatively low cytotoxicity in these cells. However, when these nanoparticles were used in combination with DOX, the cytotoxicity of DOX was significantly augmented.